Moths Pests of Potato, Maize and Sugar Beet - Khan Perveen, Farzana (IntechOpen, 2018)
This book contains four chapters. Chapter 1 is an introduction to moths. It describes their history, differences with butterflies and skippers, classification, camouflage, navigation, attraction to light, and migration. Moths are useful as bio-indicators, pollinators, dispersal of seeds and producers of useful products (silk). They are harmful as agricultural and stored-grain pests, but can be controlled biologically and with pesticides. Chapter 2 reports that among moth pests the potato tuber moth, Phthorimaea operculella Zeller, is considered one of the most important potato pests worldwide. In Chapter 3, the pathogenicity of three native isolates of the entomopathogenic fungus Beauveria bassiana were studied in different concentrations of P. operculella eggs. The most pathogenic isolate was determined on eggs in vitro. Chapter 4 highlights several case studies representing long-term field research results of moth pests in maize, Zea mays L., and sugar-beet, Beta vulgaris L.